Dance, as an art, ritual and history (ХVІІІ - ХХ of century) - Osadtsiv, Taras (Skhid, 2016)
In the article the basic aspects of choreographic art are examined in the historical aspect of ХVІІІ-ХХ of centuries. The basic aspects of concrete types of dances as reaction and ritual forms of self-expression are examined in a concrete period of historical development. Such approach gives an opportunity to understand change in perception of society of historical changes of concrete historical epoch and self-expression that is passed including through dance to us. In the article the process of evolution of choreographic art, as display of adaptation of task forces, is examined to the change of historical processes and, simultaneously their influence on the further evolution of historical development. Can be interesting to the historians, of art historian, anthropologists and sociologists.